化简求值(2a—b)( b+2a)—2(2b+a)(2b—a)其中a=1,b=2.原式=2ab+4?
更新时间:2021-10-14 10:16:46 • 作者:KRISTIE •阅读 4429
- 化简求值 -(2a-b)(a+b)-2(a-2b)(a+2b),其中a=1/2,b=-2
- 先化简,再求值:(2a b)(2a-b)-(2b a)(b-2a)其中a=-1,b=2
- 化简求值:(a+2b)(a-2b)-2(2a+b)(2a-b),其中a=1,b=2
- 化简求值:a(a+b)+(a-b)^2-(a+2b)(-b+2a)其中a=1,b=-2
化简求值 -(2a-b)(a+b)-2(a-2b)(a+2b),其中a=1/2,b=-2
-(2a-b)(a+b)-2(a-2b)(a+2b)
=-(2a²+ab-b²)-(2a²-8b²)
=-4a²-ab+9b²
=-4x1/4-1/2x(-2)+9x(-2)²
=-1+1+36
=36
先化简,再求值:(2a b)(2a-b)-(2b a)(b-2a)其中a=-1,b=2
(2a b)(2a-b)-(2b a)(b-2a)
=(2a b)(2a-b)+(2a b)(2a-b)
=4ab(2a-b)
=4X(-1)X2X(-2-2)
=32
化简求值:(a+2b)(a-2b)-2(2a+b)(2a-b),其中a=1,b=2
(a+2b)(a-2b)-2(2a+b)(2a-b)
=a^2-4b^2-2(4a^2-b^2)
=a^2-4b^2-8a^2+2b^2
=-7a^2-2b^2
=-7*1^2-2*2^2
=-7-8
=-15
化简求值:a(a+b)+(a-b)^2-(a+2b)(-b+2a)其中a=1,b=-2
解:原式=a²+ab+a²-2ab+b²-(-ab+2a²-2b²+4ab)
=a²+ab+a²-2ab+b²+ab-2a²+2b²-4ab
=3b²-4ab
当a=1,b=-2时,原式=3×2²-4×1×(-2)
=12+8
=20